Clinical significance of low result of 1-h 50-g glucose-challenge test in pregnant women. (2nd January 2019) - Oawada, Nozomi; Aoki, Shigeru; Sakamaki, Kentaro; Obata, Soichiro; Seki, Kazuo; Hirahara, Fumiki
Abstract: Objective: The objective of this study is to examine the effect of low-glucose value on the 1-h 50-g glucose challenge test (GCT) on neonatal body weight in low-risk Asian singleton pregnant women. Method: We retrospectively analyzed women who delivered a singleton neonate at term at a tertiary center and underwent GCT at 24–28 weeks of gestation between June 2001 and June 2015. The low GCT group was defined as <75 mg/dL and 75–139 mg/dL were control. We compared these two groups of maternal characteristics, small for gestational age neonate (SGA), large for gestational age neonate (LGA), low-birth weight, and macrosomia. The χ 2 test, Fisher's exact test, and Student's t test were used. Results: There were 313 low GCT groups and 4611 control. The low GCT group were younger, had lower prepregnancy body weight, higher stature, and lower prepregnancy body mass index (BMI). After adjusting these variables, the low GCT group had a lower rate of LGA and a higher rate of SGA. Neonatal body weight is more influenced by maternal physique than by low GCT result (standardized coefficient ( β ); GCT 0.071, height 0.188, prepregnancy BMI 0.143). Conclusions: Neonatal body weight was only slightly influenced by low GCT result, but markedly influenced by maternal physique, such as height and prepregnancy BMI.